Appraisal of bed linen performance with respect to sleep quality - Chanda, Tanima (Array, 2020)
Bed linen is the material laid above the mattress of a bed that serves various purposes – hygiene, warmth, protection of the mattress – and also has a decorative effect in the room. According to several studies, the type of bed linen used for our sleep has a direct effect on our health; in other words, sleep quality is the ultimate performance indicator of bed linen cloth. In this research work, a relationship between bed linen properties and sleep quality was established. Bed linens serve as a basic requirement for sleep, and assessing the right kind of sheet is an important aspect to look into. Analyzing the basic properties of bed linen is an important exercise to perform in order to provide the user with the best-quality sleep. This research focuses on deriving an equation that can be applied to calculate the objective measurement of sleep quality with respect to bed linen properties by developing a bed linen sleep quality index. Questionnaires were designed and subjective evaluation method was followed. A panel of experts was considered for a subjective rating of bed linen properties, their weightage, ranking and bed linen fabrics assessment. Coefficient of concordance was calculated to determine the agreement among the judges and a discriminant analysis was also carried out to determine the variation of the individual rating for a particular property. The results showed a high correlation between the subjective index and the objective index for the bed linen fabric samples. Thus, the objective sleep quality index could be estimated well.